MENINGKATKAN KESEHATAN DAN KEPEDULIAN SOSIAL DALAM PADA MASYARAKAT KURANG MAMPU - Farhansyah, Fani (LPPM Universitas Awal Bros, 2025)
Mass circumcision or mass circumcision activities are a form of attention aimed at underprivileged communities. From a medical perspective, circumcision or circumcision has health benefits because it removes body parts that become hiding places for dirt, bacteria viruses and others that can be harmful to health. This activity is in collaboration with Baznas Rokan Hulu, where the target participants are preschool and school-age children from underprivileged families totaling 25 children. The mass circumcision was carried out on Day Thursday Date July 17th 2025. Starting at 8 am During 1 days. The design of this activity includes: 1) Data collection on the number of mass circumcision participants, namely children from underprivileged families who live around Ujung Batu. 2) Preparing a budget plan for the needs of mass circumcision, including; the need for consumables, medicines and so on. 3) Post-circumcision evaluation, participants are asked to come for a check-up at hospital. Approximately 3 days after circumcision, to monitor the wound. The method in this activity is carried out by a personal approach to prospective mass circumcision participants. This mass circumcision activity involves various parties, medical and non-medical personnel totaling 20 people consisting of 12 people medical team and 8 people non medicalteam. After completing the circumcision process, all participants were given souvenirs and then continued with a group photo.